1994
DOI: 10.1111/j.1432-1033.1994.tb18796.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c553 from Desulfovibrio vulgaris (Hildenborough)

Abstract: An electrochemical study of the periplasmic cytochrome c553 of Desulfovibrio vulgaris (Hildenborough) is presented. The dependence of the midpoint potential on temperature and pH was studied with cyclic voltammetry. The voltammograms obtained were reversible and revealed that this cytochrome showed fast electron transfer on a bare glassy carbon electrode. The midpoint potential at pH 7.0 and 25°C was found to be 62 mV versus the normal hydrogen electrode. It was observed that the temperature dependence was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 39 publications
(37 reference statements)
4
38
1
Order By: Relevance
“…The relative high exposure of the heme to the solvent is the structural parameter modulating the low oxidoreduction potential of this cytochrome (20 mV) (8). Kinetic experiments (6) have shown that cytochrome c 553 has a rather high affinity for hydrogenase (K m 46 M) and that the electron transfer rate constant (k cat 710 s Ϫ1 ) is comparable to those generally reported in bimolecular electron transfer complexes.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The relative high exposure of the heme to the solvent is the structural parameter modulating the low oxidoreduction potential of this cytochrome (20 mV) (8). Kinetic experiments (6) have shown that cytochrome c 553 has a rather high affinity for hydrogenase (K m 46 M) and that the electron transfer rate constant (k cat 710 s Ϫ1 ) is comparable to those generally reported in bimolecular electron transfer complexes.…”
mentioning
confidence: 72%
“…Both enzymes are periplasmic and use c-type cytochromes as electron transfer partners (6). One of the oxidoreduction partners of Fe-hydrogenase is the periplasmic low potential cytochrome c 553 .…”
mentioning
confidence: 99%
“…was purified as described previously~Fauque et al, 1979;Yagi, 1979;Verhagen et al, 1994 Spectra were measured on a Hewlett-Packard 8452 diode-array spectrophotometer~absorption, 1 cm cell! and a Jasco-600 spectropolarimeter~CD, 1 mm cell for far-UV region, 1 cm cell for visible region!, at 20 8C.…”
Section: Methodsmentioning
confidence: 99%
“…Not only is it possible to study redox potentials and their dependence on parameters like temperature and pH, but also kinetic data in the form of rate constants can be obtained [1]. An important advantage of the use electrochemistry is the possibility to extend the potential window beyond the values which can be obtained in solution with chemical reductants or oxidants.…”
Section: Introductionmentioning
confidence: 99%